1973
DOI: 10.1021/ed050p186
|View full text |Cite
|
Sign up to set email alerts
|

Electronic spectra of low-symmetry d1 and d9 ion complexes

Abstract: Electronic Spectra of Low-Symmetry d' and Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

1974
1974
1978
1978

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 14 publications
0
4
0
1
Order By: Relevance
“…are equivalent only two (not three) electronic transitions for the d4 ion should be observed.30 However, extensive spectral studies on cobalt(III) complexes containing various macrocyclic and noncyclic ligands have shown that the donor strengths of the imine and pyridine ligands are significantly greater than that of a secondary amine.10,31 Since the crystal field strength of the halides is much lower than the amine donor groups31 the chromophoric symmetry of the Mn(III) compounds reduces to MA3B2C2, C2". Using the basic method developed by Companion and Komarynsky32 for calculating crystal field splitting diagrams and its extension to lowsymmetry d1 and d9 metal ions30, 33 we have determined the one-electron splitting diagram for [Mnm [15]pydieneN5X2]+.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…are equivalent only two (not three) electronic transitions for the d4 ion should be observed.30 However, extensive spectral studies on cobalt(III) complexes containing various macrocyclic and noncyclic ligands have shown that the donor strengths of the imine and pyridine ligands are significantly greater than that of a secondary amine.10,31 Since the crystal field strength of the halides is much lower than the amine donor groups31 the chromophoric symmetry of the Mn(III) compounds reduces to MA3B2C2, C2". Using the basic method developed by Companion and Komarynsky32 for calculating crystal field splitting diagrams and its extension to lowsymmetry d1 and d9 metal ions30, 33 we have determined the one-electron splitting diagram for [Mnm [15]pydieneN5X2]+.…”
Section: Resultsmentioning
confidence: 99%
“…(32) Authors will furnish this information upon request. (33) See, e.g., G. B. Thomas, Jr., "Calculus and Analytic Geometry", Addison-Wesley, Reading, Mass., 1961. (34) Since there is a decrease in the olefinic bond order upon complexation, we would expect a decrease in the v(0=C) intensity if there were no contribution to the dipole moment change from electronic motion in metal-ligand bonds.…”
mentioning
confidence: 99%
“…While this is true in principle, and could be easily implemented with the computer, the solution by hand of any determinant larger than 2 X 2 is not a fruitful exercise. In isolated instances it has been shown that closed form solutions can be written for specific geometric configurations (3,4). In this article it will be shown that the energy levels of a d1 or d9 electronic system can be written in closed form for almost every chemically significant geometry.…”
Section: Energy Levels Of D and D Ions In Chemically Significant Symm...mentioning
confidence: 96%
“…Abb. 5, Zeile 1 und 2) halten wir die quadratisch pyramidale fiir die wahrscheinlichere, weil nach [15] die Unterschiede zwischen und aE-Werten selten 20% uberschreiten.…”
Section: Experimentellesunclassified